China’s policies: post-COVID-19 challenges for the older population - Xuezhi Wei; Guoqing Han; Quansheng Wang (Global Health Action)
On 7 December 2022, the State Council of China released ‘Measures to Further Optimize the Implementation of the Prevention and Control of the New Coronavirus Epidemic’. The previous three-year dynamic zero epidemic prevention policy was then replaced with a full liberalization policy. On 5 May 2023, the World Health Organization declared that COVID-19 no longer constituted a ‘public health emergency of international concern.’ However, given the ongoing prevalence of coronavirus, emerging mutations, and the liberalization of restrictions, there are increased risks of vulnerable people contracting new variants. Low vaccination coverage among older people with compromised immune systems, puts them at further risk. The policy shift will increase pressure on already stretched health infrastructure and medical resources. This short article adds to the current debate arguing that the Chinese government should take commensurate preventive measures, including strengthening medical facilities and equipment and targeting ongoing vaccination in older people.